Financial Decision-making Abilities and Financial Exploitation in Older African Americans: Preliminary Validity Evidence for the Lichtenberg Financial Decision Rating Scale (LFDRS) - Lichtenberg, Peter A. (J Elder Abuse Negl, 2015)
This study examines preliminary evidence for the Lichtenberg Financial Decision Rating Scale (LFDRS), a new person-centered approach to assessing capacity to make financial decisions, and its relationship to self-reported cases of financial exploitation in 69 older African Americans. More than one third of individuals reporting financial exploitation also had questionable decisional abilities. Overall, decisional ability score and current decision total were significantly associated with cognitive screening test and financial ability scores, demonstrating good criterion validity. Financially exploited individuals, and non-exploited individuals, showed mean group differences on the Mini Mental State Exam, Financial Situational Awareness, Psychological Vulnerability, Current Decisional Ability, and Susceptibility to undue influence subscales, and Total Lichtenberg Financial Decision Rating Scale Score. Study findings suggest that impaired decisional abilities may render older adults more vulnerable to financial exploitation, and that the LFDRS is a valid tool for measuring both decisional abilities and financial exploitation.